To complete the square for the quadratic equation given by \(y = x^2 - 16x + 14\), follow these steps:
-
Start with the original equation:
\[ y = x^2 - 16x + 14 \] -
Focus on the quadratic and linear terms:
\[ x^2 - 16x \] -
To complete the square, take half of the coefficient of \(x\) (which is \(-16\)), square it, and then add and subtract that value inside the equation:
Half of \(-16\) is \(-8\), and \((-8)^2 = 64\). -
Rewrite the expression by adding and subtracting 64:
\[ y = (x^2 - 16x + 64) - 64 + 14 \] \[ y = (x - 8)^2 - 50 \] -
Now your equation is in vertex form \(y = a(x - h)^2 + k\), where \((h, k)\) is the vertex.
From the completed square form \(y = (x - 8)^2 - 50\), we can see that the vertex is \((8, -50)\).
So, the vertex of the parabola given by the equation \(y = x^2 - 16x + 14\) is:
\[ \boxed{(8, -50)} \]